Spiritualitas dalam Bikers Subuhan Jogja Keterkaitan antara hobi dan Ibadah - Azhar Muhibin, Zulfikar; Nurun Najwah; Muhammad Naufal Ashshiddieqi (IAIN Datuk Laksemana Bengkalis, Indonesia, 2024)
The research examines the Bikers subuhan community where in carrying out motorized hobbies there is a value of benefits ranging from time, energy and so on by inviting to go to morning prayers in congregation through the hobby method, namely motoring. The method in this research used a qualitative approach. Data collection in scientific article research by interview, observation, and literature study. As for the object of this research, the author seeks to explore the messages of how hobbies have worship value in the Subuhan Bikers community in Yogyakarta City. Thus, the results of this study in its implications have an important role, this community dismisses the perspective on the bikers community which is seen as negative, then with the presence of subuhan bikers dismisses that not all motorcycle communities are far from usefulness but there are motorcycle communities that actually have the value of worship.